Efficiency of Immunonutrition in Surgical Cancer Patients - Pelin Polat; M. Merve Tengillimoğlu Metin; Mevlüde Kızıl (Hacettepe University, 2019)
The enteral diet enriched with arginine, glutamine, omega-3 fatty acids and nucleotides named as immunonutrition reduce the duration of hospital stay after surgery, infectious complications and the risk of morbidity. These nutrients modulate inflammatory response, intestinal and immunological functions. The immune system is the primary defense against pathogenic microorganisms and cancer cells. The release of proinflammatory cytokines, the formation of reactive oxygen nitrogen species are required for the inflammatory response. Regulation of the immune system with dietary components has become as an important additional therapy in cancer patients. Although there are randomized controlled trials showing positive effects of immunonutrients in serious diseases such as trauma or burn, there is no strong evidence for these effects in cancer patients. Further prospective studies are needed to demonstrate beneficial effects of immunonutrition in cancer patients. In this review, studies evaluating the efficacy of immunonutrition in cancer patients are summarized.